Maternal and Perinatal Outcomes of Pregnancies with Uterine Leiomyomas - Kose, Caner; Korpe, Busra; Kinay, Tugba; Yilmaz Ergani, Seval; Karadeniz, Rahmi Sinan; Caglar, Ali Turhan; Engin Ustun, Yaprak (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: We aimed to determine the effect of uterine leiomyoma characteristics and cesarean myomectomy on maternal and perinatal outcomes. STUDY DESIGN: The study included patients with singleton pregnancies and uterine leiomyomas who had delivered at or beyond 24 weeks’ gestation; without comorbidities, uterine anomalies, or fetal malformations. Data from 240 patients were studied between 2012 and 2022 in the perinatology clinic of a tertiary care center. Maternal and perinatal outcomes were obtained from medical records. RESULTS: Among the women with uterine leiomyomas, 21.7% were delivered vaginally and 78.3% via cesarean section. Myomectomy was performed in 150 out of 188 (79.8%) patients undergoing cesarean section. It was found that cases with leiomyomas ≥7 cm, compared to those with <4cm, had deliveries at earlier gestational weeks (36w6/7±2d vs. 37w+6/7±2d, p=0.018) and had lower newborn birthweight (2849.44±516.74 g vs. 3237.5±350.6 g, p<0.001), longer operation time (105.92±34.78 min vs. 68.21± 22.31 min, p<0.001) and a higher rate of neonatal intensive care unit requirement (48.1% vs. 13.7%, p<0.001). In cases with ≥2 leiomyomas compared to those with single leiomyomas, gestational age at birth was smaller and birthweight was lower (p<0.05). The amount of blood loss (969.66±427.21 mL vs. 738.15±337.2 mL and 553.84±366.46 mL), duration of surgery (83.23±29.56 min vs. 64.47±17.96 min) and transfusion requirements (36% vs. 5.3% and 28.8%) were higher in women who underwent myomectomy during cesarean section than in the other women undergoing only cesarean section or delivering vaginally (p<0.05). CONCLUSION: It was found that a leiomyoma size of ≥7 cm and number of ≥2 were both associated with earlier gestational age at birth and lower birth weight. Myomectomy performed during cesarean section increased the blood loss, duration of surgery, and the need for transfusion.